Penerapan quizizz pada materi hukum pascal dalam meningkatkan respon peserta didik - Arifin, Zainul; Tatsar, Mohammad Zaky (Bulletin of Educational Management and Innovation, 2023)
Background: The research is motivated by the rapid development of the times so that there is a need for the latest innovations for students so as not to be left behind, especially in the field of technology. Purpose: The purpose of this research is about the application of Quizizz to increase students' responses to Pascal's law material. The method used in this study uses quantitative methods.. Method: The method used in this study used a survey method. with respondents totaling 19 MA Darul Ulum Karangpandan class XI MIPA students in physics subjects in the Pascal Law material. This research instrument is in the form of a questionnaire consisting of 10 statement items. Data analysis techniques using percentage descriptive analysis. Findings: The results of the analysis of student responses to the application of Quizizz are that students are interested and happy to learn to use Quizizz. This is evidenced by the results of the questionnaire data, namely the answers to the results of class XI MIPA with 19 students having an average of 78% strongly agree, 100% agree, 12% doubt, 0% disagree, and 0% strongly disagree. Based on the results of the study, it can be concluded that there is an effect of Quizizz on increasing student responses to Pascal's legal material.